Unveiling Research Publication Trends: The Bicol University Analysis (2010-2021) - Balilo Jr., Benedicto B.; Naz, Gremil Alessandro A. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – Publication is considered one of the most influential factors and requirements in a higher education institution’s (HEI’s) merit and promotion system. Some HEIs struggle in terms of publications in reputable national and international journals. This study aims to analyze the trends of research publications of Bicol University from 2010 to 2021. Method – The study is a descriptive type of research.  The publication articles from 2010 to 2021 or 237 articles were subjected to analysis to determine the research publication productivity.  The study used frequency count to determine the distribution and classification of published articles. Results – The results showed that the university has a considerably low productivity in terms of published papers in national and international-refereed journal publications which served as the basis for institutional improvement and development.  However, the BU (Bicol University) R&D Journal significantly contributed to the attainment of the institution's targets and served as a faculty option for publication. Conclusion – Bicol University needs to increase the number of publications of faculty members. Recommendations – Strong support of the top management, sustaining and building strong linkages, partnerships, and collaborations with top HEIs in the country and abroad, publication assistance, subscription to journals and databases, sourcing externally funded research, improvements in the publication incentive system, and the institutionalization of publication training and mentoring programs are recommended. Research Implications – The findings have significant implications for the university’s policies to improve publication performance and provide an environment where senior researchers should lead as prime movers or influencers to cultivate a research and publication culture in the university.